Sperm chromosome abnormalities in patients with normal karyotype and in translocation carriers: clinical relevance for assisted reproductive technology. Issue 6 (December 2020) - Magli, Maria Cristina; Crippa, Andor; Benincasa, Mara; Terzuoli, Gaia; Azzena, Silvia; Maresca, Lucia; Albanese, Cristina; Colombo, Fulvio; Ferraretti, Anna Pia; Gianaroli, Luca
Abstract: Research question: What is the proportion of chromosomally abnormal spermatozoa in men with a history of reproductive failure, including patients with normal karyotype and carriers of translocations? Should this analysis be included in a clinical setting to define the best treatment options for infertile couples? Design: Aneuploidy for chromosomes XY, 13, 15, 16, 17, 18, 21, 22 was tested by fluorescent in-situ hybridization (FISH) in 1665 samples from couples with normal karyotype having had at least three previous IVF failures, miscarriages, or both (group-A). A FISH test was also carried out in 76 samples from carriers of translocations (group B) to detect the proportion of spermatozoa with unbalanced rearrangement. Results: In group A, the lowest incidence of aneuploid sperm cells was found in men with normozoospermia (1.3%, range 0.09–6.31%) compared with men with moderate oligoasthenoteratozoospermia (2.1%, range 0.41–16.6%, P < 0.001), severe oligoasthenoteratozoospermia (4.7%, range 0.53–30.77, P < 0.001), microepididymal sperm aspiration (3.1%, range 1.19–24.24, P < 0.001) and testicular sperm extraction samples (5.8%, range 1.54–33.3, P < 0.001). In group B, the proportion of spermatozoa with unbalanced rearrangement was significantly higher in reciprocal (63%, range 10.0–87.6%) than in Robertsonian translocations (16%, range 4.3–51.0%, P < 0.001). Conclusions: Patients with poor prognosis of term pregnancy tend to generate high proportions of chromosomally abnormal spermatozoa, especially in severe male factor cases. Corresponding frequencies occur at wide ranges; therefore, the FISH test is needed to assess the proportion of spermatozoa with altered chromosome condition. A flowchart, which included the FISH test, was designed to assist clinicians guide couples with poor prognosis of pregnancy, on the most indicated treatment options.